2009
DOI: 10.1021/es803141m
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Groundwater Arsenic Occurrence and Association with Bedrock Geology in Greater Augusta, Maine

Abstract: In New England, groundwater arsenic occurrence has been linked to bedrock geology on regional scales. To ascertain and quantify this linkage at intermediate (100-101 km) scales, 790 groundwater samples from fractured bedrock aquifers in the greater Augusta, Maine area are analyzed. 31% of the sampled wells have arsenic >10 μg/L. The probability of [As] exceeding 10 μg/L mapped by indicator kriging is highest in Silurian pelite-sandstone and pelite-limestone units (~40%). This probability differs significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 24 publications
3
63
0
Order By: Relevance
“…Our other survey study that followed up with 256 households who had all received test results of As >10 μg/L between 2006–2010 (Flanagan et al, this issue) found similar rates of forgetting; 31% did not remember their As test results and 14% recalled incorrectly, more often underestimating their As level. In addition to As (Yang et al, 2009; Nielsen et al, 2010), state lab testing and Columbia University testing have shown that the greater-Augusta area of Central Maine has high Rn occurrence along with other natural contaminants in the groundwater. (Yang et al, 2014), so it is concerning to find that 22% of households in this area may have never tested their well water for anything.…”
Section: Discussionmentioning
confidence: 99%
“…Our other survey study that followed up with 256 households who had all received test results of As >10 μg/L between 2006–2010 (Flanagan et al, this issue) found similar rates of forgetting; 31% did not remember their As test results and 14% recalled incorrectly, more often underestimating their As level. In addition to As (Yang et al, 2009; Nielsen et al, 2010), state lab testing and Columbia University testing have shown that the greater-Augusta area of Central Maine has high Rn occurrence along with other natural contaminants in the groundwater. (Yang et al, 2014), so it is concerning to find that 22% of households in this area may have never tested their well water for anything.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2006 and 2011 the Columbia University Superfund Research Program (SRP) and the Maine Geological Survey (MGS) tested 1,428 domestic well water samples in 17 towns encompassing over 1500 km 2 (Yang et al, 2009; Yang, 2010). Over 95% of these samples were collected from drilled wells, which are at higher risk for As (Ayotte et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Arsenic has acute and chronic toxic and carcinogenic effects on aquatic organisms and humans (Oremland and Stolz, 2003). Elevated levels of arsenic present in the environment have caused public concern (Yang et al, 2009). Arsenic is ubiquitous in groundwater, soil and sediments as a result of natural processes including mineral weathering, dissolution and geothermal activities (Manning et al, 1998;Yamamura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%